2016
DOI: 10.1111/jpn.12448
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of sunflower oil or linseed oil in equine compound feedstuff: 1 Effects on haematology and on fatty acids profiles in the red blood cells membranes

Abstract: Eight trained horses (6 mares - 2 geldings, 6 Selle Français, 2 Trotteur Français, 12 ± 5.8 years old, 538 ± 72.5 kg) were offered three diets to potentially affect haematology and the fatty acids (FA) profiles in red blood cells (RBC) membranes. The control diet was composed of 50% hay and 50% concentrate containing mainly rolled barley (48%) and whole spelt (48%). In the case of sunflower oil diet, sunflower oil (62.0% of α-linoleic acid, LA) was incorporated at a rate of 8% and substituted by an equal propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Horses have low fatty acid elongation activity, which is important for the inflammatory response, and there is speculation that linseed as a source of omega-3 PUFA may decrease signs of laminitis by inhibiting inflammatory mediators [17]. In a quite recent study [18], increased concentrations of red blood cells, haemoglobin and haematocrit, as well as improved n-3 fatty acid profiles, were reported as a result of linseed oil supplementation. Vineyard et al [19] found that supplementing horses with milled linseed resulted in pronounced early inflammatory responses to phytohaemagglutinin injections.…”
Section: Introductionmentioning
confidence: 99%
“…Horses have low fatty acid elongation activity, which is important for the inflammatory response, and there is speculation that linseed as a source of omega-3 PUFA may decrease signs of laminitis by inhibiting inflammatory mediators [17]. In a quite recent study [18], increased concentrations of red blood cells, haemoglobin and haematocrit, as well as improved n-3 fatty acid profiles, were reported as a result of linseed oil supplementation. Vineyard et al [19] found that supplementing horses with milled linseed resulted in pronounced early inflammatory responses to phytohaemagglutinin injections.…”
Section: Introductionmentioning
confidence: 99%
“…Their importance, especially the n-6 to n-3 ratio, in equine physiology may include improving exercise tolerance, reducing inflammation, and improving reproductive function. In the experiment by Patoux and Istasse (2016) supplementation of sport horse diets with sunflower oil slightly increased the amount of C18:2 n-6 and C22: 4 n-6 acids, while a decrease was observed in the case of C16:1 n-7, C20:3 n-6 and C20:4 n-6. A similar effect on n-6 fatty acid profiles was observed when linseed oil was supplemented.…”
Section: Discussionmentioning
confidence: 89%